(untitled) (Olhar de Professor, 2023)
The article addresses part of a qualitative research, from the implementation of the Reading Carousel pilot project, with a group of students the 4th year of Elementary School I, in a public school in Poços de Caldas- MG. The study investigated whether the contributions to awakening the pleasure for reading in the student reader, based on the Reading Carousel, managed to break with the positivist and mnemonic standard of school reading. The theoretical foundation was based on a multidisciplinary approach and methodologically, action research was found to be an important possibility of effectiveness in the attempt to understand the social, cultural, and educational practices that permeate the reading practice. The results obtained revealed that it is possible to contribute to reading fruition through the Reading Carousel methodology. The intention is to expand the scope of this research with the Reading Carousel Workshop as a proposition for the continuing Education of Kindergarten and Elementary School teachers.